2013
DOI: 10.12739/nwsa.2013.8.2.1c0583
|View full text |Cite
|
Sign up to set email alerts
|

Öğrenci̇ Kontrol Strateji̇si̇ne Yöneli̇k Öğretmen Tutumlari

Abstract: THE TEACHER ATTITUDES TOWARD THE LEARNER CONTROL STRATEGY ABSTRACTThe major purpose of this research was to examine the uses' level of learner control strategy by teachers as general in their courses. For this study, data were collected from 219 state primary school teachers, including Turkish, English, math, science, social science, religion and morality, and computer-technology teachers in the province of Adana, Turkey, during the 2010-2011 academic year. The data were gathered by administering the learner c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Since in previous research in southern Tanzania the researchers found that there is a high degree of sensitivity in being able to recruit out-of-school youth to participate in research (see Roberts et al, 2015), participants for this study were identified in rural Mtwara region villages where one of the researchers had developed trusting and lasting relationships. A qualitative approach was appropriate because we sought to gain an in-depth understanding about how the decisions out-of-school youth make to learn new information are influenced by their schooling experience or external factors such their community, government, or higher education institutions (Kutlu & Korkmaz, 2013;Marshall & Rossman, 1999). We employed a semi-structured format for our interviews to enable us to gain a more nuanced understanding about the processes out-of-school youth use to learn and the type of information they acquire.…”
Section: Methodsmentioning
confidence: 99%
“…Since in previous research in southern Tanzania the researchers found that there is a high degree of sensitivity in being able to recruit out-of-school youth to participate in research (see Roberts et al, 2015), participants for this study were identified in rural Mtwara region villages where one of the researchers had developed trusting and lasting relationships. A qualitative approach was appropriate because we sought to gain an in-depth understanding about how the decisions out-of-school youth make to learn new information are influenced by their schooling experience or external factors such their community, government, or higher education institutions (Kutlu & Korkmaz, 2013;Marshall & Rossman, 1999). We employed a semi-structured format for our interviews to enable us to gain a more nuanced understanding about the processes out-of-school youth use to learn and the type of information they acquire.…”
Section: Methodsmentioning
confidence: 99%